Влијанието на лидерството врз развојниот процес на тимот и неговите членови за ефективен менаџмент на организацијата - Ѓуров, Лазар (Економски факултет, УКИМ, Скопје, 2011)
Today, the need for quality leadership, in the framework of organizations is more than necessary. Although the process of leadership is mainly universal and identical, still the modern conditions of living in great measure complicate the successful realization of it. The global accessibility to information, the open markets, the transition processes, the new system of values, the consistent uncertainty created in the society, the different level of satisfied needs and the emphasized individuality are only few of the many things which influence the efficiency of the leadership and the management at the organizations. The fact that transformational leadership today is most present in theoretical elaboration of the phenomenon leadership, on the account other approaches, shows that the transformational processes of individuals in regard to their value system, beliefs, attitudes, understandings and principles of their personality, is a modern application of the leadership in its most vital sense. The success of each organization is mainly based on the functionality of each individual, along with the primary groups of teams on all levels in the organizational hierarchical structure. The team and the feeling of belonging to the organization is defined by the level of involvement in the working process, the desire for self-giving and sacrifice, self-encouragement/ initiation and motivation, the care for the company through giving ideas and suggestions for improvement of work, etc. Due to this/ Thus, besides the leader‟s dedication on fulfilling the goal, equally important aspect, which will guarantee success and fast fulfillment of the goal in long-term running of the organization as a whole, is the influence of the leaders directed towards the development of the individuals in the organization and the influence of the leaders in the development of teams. Due to these facts, this paper puts particular emphasis to the interdisciplinary research of the conditions and the possibilities of the leader to influence the development of the individuals in the framework of everyday performance of the organization. The process of development of an individual was explored from psychological, social and pedagogical perspective. All important aspects of modern approaches for motivation, which are based on the need for development and self-improvement, were also observed. The summary of all aspects for personal development was done through the prism of discovering the potential of the individual, with special emphasis on the possibilities which the leader has in stimulating this process, in everyday work of the organization. Identically important is the research on dynamics of the groups and the phases through which an incompatible group undergoes and becomes an efficient, compatible team. All group processes which can accelerate or slow down the development of the group, with special accent on the role of the leader and the possibility to influence the successful realization of the development process, were also explored. The paper presents the results from the research conducted among members of teams and their leaders, at three organizations in R. Macedonia, in reference to the influence of leadership on the development of individuals and teams.
The influence of leadership to the developmental process of team and its members for effecive management of the organizatioн
Докторска дисертација одбранета во 2011 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: leader, development, leadership, management, individual development, group, team, organizational behavior